Cite them right : the essential referencing guide - Pears, Richard; Shields, Graham J. (New York : Bloomsbury Academic, 2022)
"Now in its twelfth edition, this essential resource is the go-to text for students and authors who want to accurately reference sources and avoid plagiarism in their work"--
Includes bibliographical references and index.
Book Finder
Keywords: Bibliographical citations